FOOD AND NUTRITION SURVEILLANCE SYSTEM: FOOD CONSUMPTION OF CHILDREN AGED 2 TO 4 BETWEEN 2018-2022 - Cavalcante, Francylene Barbosa; Uchoa de Mesquita, Armênia (Cadernos ESP, 2025)
The aim of this study was to describe the consumption of ultra-processed foods in children aged 2 to 4 between 2018 and 2022. This is an observational, descriptive study using secondary data from SISVAN. The collection took place from February to March 2023. The study population consisted of 1,067,357 children in Brazil/Northeast/Ceará and São Gonçalo do Amarante. The consumption of ultra-processed foods among children in Brazil in 2021 was 88% and 86% in the Northeast, while it was 83% in Ceará and 81% and 92% and 90% in São Gonçalo do Amarante. Given the huge range of ultra-processed foods that are made available to children in this stage of life, it is important to carry out research, discussions and reflections on Food and Nutrition Surveillance in pre-school, with the aim of implementing public policies or reinforcing those that already exist.